Performance Evaluation IT Governance on Universities: COBIT 2019 Approach with Measurement Capability Levels - Marcela, Elisabet Dela; Melissa Indah Fianty (The Indonesian Journal of Computer Science, 2023)
The utilization of the Peoplesoft Campus Solution (MyUMN) technology, which has become excessively outdated, necessitates an evaluation, development, and rejuvenation of MyUMN to address any occurring issues with definitive solutions. An assessment of the Information Technology governance capability level is carried out using the COBIT 2019 framework. This research focuses on the following specific objectives: BAI03 (Managed Solutions Identification and Build), BAI06 (Managed IT Changes), and BAI07 (Managed IT Change Acceptance and Transitioning). The measurement results reveal that the capability levels for all three objectives are at level 2, while the targeted capability level is at level 4. Consequently, there exists a gap between these two levels. Recommendations encompass prioritizing the documentation of application development and conducting routine reviews of all completed change requests to ensure the alignment of change requests